MANIFESTATION OF THE ATTENTION PROCESS IN CHILDREN WITH SPEECH IMPAIRMENT - Narziyeva Sarvinoz Jamshid qizi (Web of Journals Publishing, 2024)
This article discusses the features of the manifestation of the attention process, one of the cognitive processes in children with speech impairments.
Keywords: Attention, productive, neurotic stuttering, neurosis stuttering, cognitive, cognitive and affective fronts, genetic, voluntary, involuntary.